(untitled) (Journal Of Educational and Psychological Researches, 2011)
The current study aimed to know the reasons for the reluctance of students to apply mathematics department in the Iraqi universities. In order to achieve the objective of the study the researchers a tool numbers of 4 - axes included 40 - paragraph, distributed as follows: - Set the first axis causes that relate to the student, the 14 paragraph. - The second axis includes clauses concerning teacher and the number of paragraphs of Article 9, paragraph. - Axis III contains clauses concerning the nature of mathematics and a number of paragraphs 11 paragraphs. - The fourth, which included reasons related to classmates and close and the number of paragraphs 6, paragraph. The resolution offered on a group of arbitrators has been amended some of the paragraphs and got the approval of 85% of the arbitrators on the affiliation of the paragraphs, which put into it. Used psychometric properties of reliability and validity of the mining and construction indicators endorsed the adoption of the para-class correlation coefficient as extracted total consistency by re-test (test-retest) and indicators were acceptable and statistically significant at the5% level. Applied the questionnaire on a sample of the teaching staff numbered around 20 by 10 pedagogy and teaching pedagogy from the University of Baghdad and 10 pedagogy and teaching of the University of Technology and took into account the different levels of scientific teacher assistant, teacher, professor, assistant professor. The sample was selected from students with 60 students by 30 students from Baghdad University and 30 students, University of Technology was selected randomly from students and from sections of the new mathematics in the education and scientific collage. The results showed that the most common reasons unit is (a sense of student rigid mathematics and its isolation from development), and mathematics to deal with a banana so you need from the student focus and mental effort significantly, has also developed some of the recommendations including reconsideration of the decisions of the mathematics curriculum, and expand employment opportunities for graduates, and the development of teaching competence of teachers